Sulfate reduction and its important role in organic carbon mineralization in sediments of the Pearl River Estuary. (5th October 2021) - Yin, Xijie; Lin, Yunpeng; Li, Yunhai; Wang, Liang; Sun, Zhilei; Li, Guogang
Abstract: The sulfate reduction process plays an important role in the early diagenesis of organic matter in the estuarine and coastal sediments. In this study, the sulfate reduction rates (SRR) were determined by the 35 SO4 2− radioactive tracer method, and the SO4 2−, CH4, Cl − of sediment porewater and total organic carbon (TOC), temperature, and redox potential (Eh) of sediment were determined simultaneously at three stations (QA, HQ, and GS) in different sedimentary environments of the Pearl River Estuary to study the sulfate reduction process and its important role in organic matter mineralization. The results show that SRR was mainly controlled by the content and availability of organic matter in sediments of the Pearl River Estuary. The consumption of sulfate mainly included the organic matter mineralization on the upper sediments and the anaerobic oxidation of methane (AOM) driven by sulfate in the sulfate-methane transition zone (SMT), which formed two peaks in the SRR profile, respectively (stations HQ and GS). Affected by physical disturbance, there was only one SRR peak formed above the SMT at station QA. The results of flux calculations for AOM and sulfate reduction show that the contributions of AOM to total sulfate reduction were 7.04 %, 5.46 %, and 42.0 % at stations QA, HQ, and GS, respectively, which were also controlled by the content and availability of organic matter in sediments. The depths of SMT in sediments of stations QA, HQ, and GS were 25, 30, and 213 cm, respectively, which were controlled by the input of organic matter and sulfate concentration in sediments. The calculation results show that total fluxes of sulfate reduction were 22.7, 35.3, and 3.9 mmol m −2 d -l at stations QA, HQ, and GS, respectively, and the rates of organic carbon mineralization by sulfate reduction were 45.4, 70.6, and 7.8 mmol m −2 d -l . In the estuarine mouth (station GS) with relatively weak hydrodynamic force and deep water, the burying efficiency of organic matter in sediment was higher than that in the brackish coast (station HQ); whereas the burial efficiency of organic matter in sediment cannot be comprehensively estimate in the upper estuary (station QA) due to the existence of the fluid mud layer. These findings contribute to a comprehensive understanding of the biogeochemical cycling process of sulfate and methane in sediments of the Pearl River Estuary. Graphical abstract: Image 1 Highlights: SRR is mainly controlled by the content and availability of organic matter in sediment. The SMT depth is controlled by organic matter input and sulfate concentration. Contributions of AOM to SR at station GS are higher than that at station QA and HQ. The burying efficiency of organic matter in river mouth is higher than that in brackish coast.